The control of conventionality and its binding nature in the Colombian Contentious Administrative Jurisdiction - Elsibed Carmona Gomez; Adriana Marcela Rodriguez Bolaños (Postulados: Revista Sociojurídica)
The control of conventionality is a term recently accepted and conceived as a mechanism for the protection of human rights; therefore, the Inter-American Court of Human Rights has been conceptualizing, developing and establishing application parameters with its decisions based on specific cases. Due to the above, in this investigation an analysis will be carried out on the control of conventionality and its binding nature in the Colombian Contentious Administrative Jurisdiction, taking into account the pronouncements issued by the Inter-American Court of Human Rights, the Council of State and its effects on the Colombian legal system